The 3rd AGILE Terrestrial Gamma‐ray Flashes Catalog. Part II: Optimized Selection Criteria and Characteristics of the New Sample. Issue 11 (10th June 2020) - Maiorana, C.; Marisaldi, M.; Lindanger, A.; Østgaard, N.; Ursi, A.; Sarria, D.; Galli, M.; Labanti, C.; Tavani, M.; Pittori, C.; Verrecchia, F.
Abstract: We present in this work the third catalog of terrestrial gamma‐ray flashes (TGFs) by the AGILE mission and the new search algorithm that was developed to produce it. We firstly introduce the new selection criteria, designed from the characteristics of WWLLN‐identified TGFs, and then applied on all data from March 2015 to September 2018. Association with sferics was performed by an independent search, described in a companion paper by Lindanger et al. (2020, https://doi.org/10.1029/2019JD031985 ). This search showed that many TGFs were not recognized by the existing selection algorithm, hence the need for this work. Several new selection criteria were tested and are compared in this paper. We then present the chosen selection criteria and the obtained sample, which includes 2, 780 events and represents the most extensive TGF catalog available for the equatorial regions. Finally, we discuss the characteristics of this sample, including geographic distribution, intensity and duration, and seasonal variations. Key Points: A new set of selection criteria for AGILE TGFs is designed based on a lightning‐associated TGF sample A sample of 2, 780 events detected by AGILE over a 3‐year period is presented, the largest sample to date across the equator Geographical, local time, and seasonal variability of the sample is discussed